The Influence of Multimedia Learning and Students’ Learning Motivation toward Biology Learning Outcomes : English - H, Nurhikmah; Lu'mu, Lu'mu; Ridwan, Muhammad (Universitas Nahdlatul Ulama Blitar, 2025)
This study seeks into the effect of multimedia-based learning on the biology learning outcomes in the excretory system topic and influence of learning motivation on biology learning outcomes in the excretory system topic. This is a pre-experiment design without a control group, involving a sample of 20 students. The research procedure for this one-group pre-test-post-test pre-experiment consists of four stages: (1) preparation or planning, (2) implementation of research/observation, (3) processing and analyzing results and testing research hypotheses, and (4) drawing conclusions from the research findings. There is a significant impact of multimedia-based learning on the biology learning outcomes in the excretory system topic for eighth-grade students at a junior high school in West Sulawesi Province. 2. There is a significant influence of learning motivation on biology learning outcomes in the excretory system topic through the application of multimedia-based learning for eighth-grade students at a junior high school in West Sulawesi Province. The multimedia-based learning has a very significant effect on learning motivation because of understanding and better understanding of the retention of learning materials. Multimedia-based learning also allows students to learn in a more visual, auditory, and kinesthetic way. In this case, multimedia can help facilitate different learning styles in students, so that they can more easily understand and remember learning materials.